The Zulu-Boer War, 1837-1840 - Leśniewski, Michał (History of warfare, 2021)
"This book offers an in-depth examination of the conflict of 1838 to 1840 between the Zulus and the Boers. Leśniewski reflects on the established historiography and reappraises some key conceptions of the war. The conflict has often been seen as a colonial war, with the Zulus cast into the role of either villains or victims. Drawing on written primary sources and Zulu oral tradition, the author instead argues that the war was a struggle between an established regional power aiming to defend and consolidate its position and an incoming power seeking land, settlement, and local supremacy"--